The travels of M. de Thévenot through the thug archive - ní Fhlathúin, Máire (Cambridge University Press, 2001)
The campaign against thuggee in 1830s India produced a set of widely-circulated accounts of the origins and practices of thugs. In these works (both popular and scholarly), a very small amount of primary information was continually recycled throughout the nineteenth and twentieth centuries. The changes visible in the manner of deployment of this information are indicative of progressive re-formulations of the narrative of the history of thuggee, and the larger history of British India. This process is examined through a study of the incorporation of an extract from The Travels of M de Thévenot into the Levant into the historical archive, which concludes that any re-appraisal of history must incorporate a consideration of the narrative underlying the production of the records, as well as the records themselves.